X-ray micro-computed tomography reveals a unique morphology in a new click-beetle (Coleoptera, Elateridae) from the Eocene Baltic amber - Kundrata, Robin; Bukejs, Andris; Prosvirov, Alexander S; Hoffmannova, Johana (Scientific reports, 2020)
Beetle fossils are a rich source of information about the palaeodiversity and evolutionary history of the order Coleoptera. Despite the increasing rate of fossil research on click-beetles (Coleoptera: Elateridae), the most diverse group in the superfamily Elateroidea, their fossil record has remained largely unstudied. This may be caused by the combination of their rather uniform external morphology and the suboptimal state of preservation and visibility in most fossil specimens. Here, we used X-ray micro-computed tomography to reconstruct the morphology of an interesting click-beetle from Eocene Baltic amber, which had some principal diagnostic characters obscured by opaque bubbles and body position. Our results suggest that the newly described Baltelater bipectinatus gen. et sp. nov. belongs to tribe Protelaterini within subfamily Lissominae. Since Protelaterini have a predominantly Gondwanan distribution, our discovery is of a great importance for the historical biogeography of the group. Very distinctive are the bipectinate antennae with 11 antennomeres and with rami beginning on antennomere IV, which are not found in any recent Elateridae. The discovery of a new click-beetle lineage from European Eocene amber sheds further light on the palaeodiversity and historical diversification of the family as well as on the composition of the extinct amber forest ecosystem.
Keywords: brouci; lesy; Amber; Baltic States; Animals; biologická evoluce; Paleontology; zkameněliny; zvířata; rentgenová mikrotomografie; Biological Evolution; pobaltské republiky; Coleoptera; Fossils; jantar; Forests; X-Ray Microtomography; paleontologie